Investigating the Relationship between Workload-Resources and Exhaustion of Nurses and Police Officers in Namibia - W.R., Pieters; A.A., Van Heerden (Journal of Economics and Behavioral Studies, 2018)
A lot has been published on burnout within the service industry; however, an in-depth investigation of job stressors and burnout in both the safety and health sectors of Namibia has been left unexplored. This study investigated the relationship between job demands-resources and burnout. Burnout occurs when an individual is exposed to emotional and interpersonal stressors on the job (exhaustion, cynicism and professional efficacy). Job demands require continuous efforts and job resources are aspects of the organisation that are helpful in achieving goals, reducing costs of job demands and stimulating growth and development. The sample is made up of police officers (n=482) and nursing staff (n=672) from various regions within Namibia (n=1154). Results were analysed using the SPSS (version 24) to assess the relationships between the variables. The results revealed exhaustion had a relationship with the workload, resources and organisational support. Lower levels of workload, accompanied with higher levels of resources and organisation support would reduce exhaustion. The workload can be managed by making using of timemanagement training, improving delegation, and by ensuring the employees have mentors and supervisory support. Training opportunities improve work resources and reduce work stress. Healthy coping strategies, like being active and meditation help to alleviate stress (exhaustion). Having healthy work relations enhances organisational support and improves coping mechanisms of employees.